Heavy Metals Pollution Assessment of the Water in Al-Quds Power Plant in Baghdad - Hussain, Hadeel M.; Abdulkader , Saad Z. (Iraqi Journal of Science, 2021)
Sixteen water samples were collected from the operation units of the Al-Qudspower plant, north Baghdad city and the surrounding trocars, surface andgroundwater, and analyzed to assess the resulting pollution. The samples wereanalyzed for heavy metals (As, Cd, Cr, Cu, Mn, Mo, Ni, Pb, Sb, Se, U and Zn) byusing inductively coupled plasma- mass spectrometry (ICP-MS). The results werecompared with local and international and standard limits. Heavy metals analysis ofthe water samples shows that water of operation units and trocars have meanconcentrations of As, Cd, Cr, Cu, Mo, Pb, Sb, Se, U and Zn were within or lowerthan the national and world limits, while Mn and Ni were higher than these limits.Concentrations of these elements in the surface water were within the safe limits. Inthe groundwater samples As, Cd, Cr, Cu, Mo, Sb, Se, U and Zn were within thepermissible limits while Ni, Mn and Pb were higher than the permissible limitsindicating the effect of anthropogenic activities. The collected samples submitted tohealth risk assessment to evaluate the actual adverse effects of contaminants tohumans, the results of HQs ingestion of all elements (except As for child) aresmaller than 1, suggesting little hazard. In addition, HQs dermal in all studiedelements for adult are below1, indicates no hazards for dermal absorption. Overall,HI of As and Mn for child exceeded 1. Comparison between values of HQ ing foradults and children shows that children are more susceptible to adverse to healtheffects than adults. These results necessitate a search of the means of treatment andreduce pollution with heavy metals in the industrial areas.